1991
DOI: 10.1159/000195925
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled and Oral Salbutamol: How Effective in the Prophylaxis of Asthma?

Abstract: Inhaled and oral salbutamol were compared in 12 asthmatic patients for prophylaxis in antigen-induced asthma. The patients were pretreated with 0.2- and 1.0-mg doses of inhaled salbutamol and with the standard oral 4- and 8-mg slow-release (SR) salbutamol preparations. Bronchodilatation was monitored over the ensuing 3 h and protection against antigen challenge at the end of the period. On each study day the degree of baseline airway hyperreactivity was determined by histamine challenge. Precautions were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The protective effect of 200 pg salbutamol in terms of PD,5 might have been more equal to that of 12 pg formote rol if the time interval after the challenge had been shorter than 3 h. The effect of salbutamol administered as a single inhaled dose is shown to be at least 3 h [20,24]. Thus the time points selected for the present study seemed to be justified.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The protective effect of 200 pg salbutamol in terms of PD,5 might have been more equal to that of 12 pg formote rol if the time interval after the challenge had been shorter than 3 h. The effect of salbutamol administered as a single inhaled dose is shown to be at least 3 h [20,24]. Thus the time points selected for the present study seemed to be justified.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, Nix et al [19] have shown that formote rol has a significantly better protective effect than terbutaline, on metacholine-induced bronchoconstriction for 2 h after drug administration. However, the protective effect of (T-agonists on bronchocontriction is shown to be doserelated during antigen challenge [24].…”
Section: Discussionmentioning
confidence: 99%